In silico investigation of the effects of gentamicin on lysosmal lipid degradation and the transport system between lysosomes and smooth endoplasmic reticulum - Mitovic, Nikola; Spasic, Svetolik; Jovanovic, Nikola; Stanojevic, Marija; Paunovic Pantic, Jovana; Kovacevic, Sanjin; Gostiljac, Drasko; Jovicic, Vladimir; Jevtovic, Jelena; Nesovic Ostojic, Jelena (Medical Research, 2026)
Introduction: Gentamicin, an aminoglycoside antibiotic has limited clinical use due to accompanying side effects: nephrotoxicity and ototoxicity. The damage caused by gentamicin accumulates over time and leads to cell death. Cells of renal proximal tubules are most affected, as are hair cells of the inner. One of the presumed mechanisms of toxicity is phospholipidosis, a disorder characterized by accumulation of phospholipids in the cell. The Aim: The aim of this study is to investigate, in silico, the mechanism of gentamicin action in the development of phospholipidosis through interactions with key proteins responsible for lipid transport between the smooth endoplasmic reticulum and late endosomes, as well as enzymes involved in lipid degradation. Material and Methods: We defined target proteins in the KEGG database and their expression profiles and tissue specificities were examined through the Human Atlas database. Nine proteins met the final criteria and were further examined by molecular docking using AutoDock Vina program. Results: Most of the examined proteins showed high expression in the kidney and corresponding structures of the central nervous system. Docking analysis indicated that the interaction between gentamicin and ORP1L protein exhibited the lowest Gibbs free energy value of - 8.1kCal/mol, while the STARD3 protein had the highest Gibbs free energy value of -5.2kCal/mol. Amino acid sequences to which gentamicin binds on the selected proteins were similar within the same protein families. Conclusion: Observed under in silico conditions, gentamicin interacts with proteins that participate in lysosomal lipid degradation and transport between lysosomes and smooth endoplasmic reticulum.